Application of adomian decomposition method to solving nonlinear differential equations - Sekgothe, Nkhoreng Hazel (My University, 2021)
Modelling with differential equations is of paramount importance as it provides pertinent insight into the dynamics of many engineering and technological devices and/or processes. Many such models, however, involve differential equations that are inherently nonlinear and difficult to solve. Many numerical methods have been developed to solve a variety of differential equations that cannot be solved analytically. Most numerical methods, however, require discretisation, linearisation of the nonlinear terms and other simplifying approximations that may inhibit the accuracy of the solution. Further, in some methods high computational complexity is involved. Due to the importance of differential equations in modelling real life phenomena and these stated shortfalls, continuous pursuit of more efficient solution techniques by the scientific community is ongoing. Industrial and technological advancement are to a larger extent dependent upon efficient and accurate solution techniques. In this work, we investigate the use of Adomian decomposition method in solving nonlinear ordinary and partial differential equations. One advantage of Adomian decomposition method that has been demonstrated in literature is that it achieves a rapidly convergent infinite series solution. The method is also advantageous in that it does not require one to linearise and discretise the equations as is done with other numerical methods. In our investigation, among other important examples, we will apply the Adomian decomposition method to solve selected fluid flow and heat transfer problems. Fluid flow and heat transfer models have pertinent applications in engineering and technology. The Adomian decomposition method will be compared with other series solution methods, namely the differential transform method and the homotopy analysis method. The desirable attributes of the Adomian decomposition method that are stated in literature have been ascertained in this work and it has also been demonstrated that the Adomian decomposition method compares favourably with the other series solution methods. It has also been demonstrated that in some cases nonlinear complexity results in slow convergence rate of the Adomian decomposition method.
Thesis (M. Sc. (Applied Mathematics)) -- University of Limpopo, 2021
Keywords: Adomian decomposition method; Nonlinear differential equations; Differential equations, Nonlinear; Equations -- Numerical solutions